Identification of steroid hormones and fatty acids during gonadal maturation of spiny lobster Panulirus homarus. Issue 2 (3rd April 2019) - Adiputra, Yudha Trinoegraha; Zairin jr, Muhammad; Suprayudi, Muhammad Agus; Manalu, Wasmen; Widanarni,
ABSTRACT: Information on steroid hormones and fatty acids that play roles in lobster reproduction is still very limited although the data are indispensable to seed production in hatchery. The study was designed to identify steroid hormones and fatty acids during gonadal maturation of spiny lobster ( Panulirus homarus ). Male spiny lobsters were treated with and without thyroxine injection. Female spiny lobsters were treated with and without eyestalk ablations during mature and immature gonad developments. Androst-5-en-17-one, 3β (androst) and estran-3-one, 17β (estran), two steroid hormones were identified at different levels of gonadal maturity of spiny lobsters. High concentrations of androst and estran were detected in the male spiny lobsters treated with thyroxine injections. Estran showed high concentrations in female brood stock of spiny lobsters during oogenesis stages both without eyestalk ablation and with ablation of one or two eyestalks, except in the immature female gonads. It was found that stearic acid was the highest and dominant fatty acid in mature male spiny lobster. Stearic acid, oleic acid, palmitic acid and caprylic acid were fatty acids with high concentrations in immature and mature female spiny lobsters. After 30 days in captivity, only stearic acid and oleic acid were found dominantly in eyestalk ablated mature female spiny lobsters.